DriveEasy: Car Rental Management System - Gunasekaran, Tiviyarsiri; Arbain, Siti Hajar (Applied Information Technology And Computer Science, 2025)
DriveEasy: Car Rental Management System aims to transform car rental operations and overcome the challenges of manual processes observed at Nadim Car Rental in Batu Pahat, Malaysia. The current system depends on inefficient paperwork, leading to errors, delays, and customer dissatisfaction. The primary objective of this study is to develop a web-based using an object-oriented approach and test it in alpha phases. The scope focuses on the specific needs of Nadim Car Rental with the involvement of internal stakeholders. This system is focused on different user roles and optimizes customer data, reservations, and maintenance. The methodology used to implement the car rental management system is the Rapid Application Development (RAD) model. The main results are improved operational efficiency, cost reductions, and a better customer experience. This abstract establishes a foundation for future innovations and improvements, suggesting a significant shift in car rental management practices.